PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF JIGSAW - RATNANINGSIH RATNANINGSIH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The method applied by the teacher in Civics learning is still conventional, tends to use the verbalistic lecture method, resulting in passive students, lack of enthusiasm, and low student learning outcomes. To improve the learning process and results, the teacher responded by applying the Jigsaw cooperative learning model and applying it in the form of Classroom Action Research (CAR). The purpose of this Classroom Action Research is to increase the activeness and learning outcomes of Civics. The action is carried out through three cycles. Each cycle includes four activities, namely (1) Planning, (2) Acting, (3) Observing, and (4) Reflection. One cycle is carried out in two to three meetings. Based on the results of data analysis, findings, and discussions that have been carried out, it can be concluded that the actions taken in class VIIIA to increase the activity and learning outcomes of Civics through the Jigsaw cooperative learning model were successful because the research performance indicators were met. Before the action using the Jigsaw cooperative learning model, the activeness of class VIIIA students was 73.43 in the active category and at the end of the third cycle of 79.10 in the very active category, an increase of 5.67 (an increase of 8%). Before the action, the KKM achievement in the class was 10%, after the first cycle of action it became 54.33% (an increase of 43.33%), after the second cycle of action it became 76.67% (an increase of 23.34% from the first cycle), and after the third cycle of action it increased to 93.33% (an increase of 16.66% from cycle II). ABSTRAKMetode yang diterapkan guru dalam pembelajaran PKn masih bersifat konvensional, cenderung menggunakan metode ceramah yang verbalistik, sehingga mengakibatkan siswa pasif, kurang bersemangat, dan hasil belajar siswa rendah. Untuk memperbaiki proses dan hasil belajar disikapi guru dengan menerapkan model pembelajaran kooperatif Jigsaw dan mengaplikasikannya dalam bentuk Penelitian Tindakan Kelas (PTK). Tujuan Penelitian Tindakan Kelas ini yaitu untuk meningkatkan keaktifan dan hasil belajar PKn. Tindakan dilaksanakan melalui tiga siklus. Setiap siklus meliputi empat kegiatan yaitu (1) Perencanaan (Planning), (2) Pelaksanaan (Acting), (3) Pengamatan (Observing), dan (4) Refleksi (Reflection). Satu siklus dilaksanakan dalam dua sampai tiga kali pertemuan. Berdasarkan hasil análisis data, temuan, dan pembahasan yang telah dilakukan dapat disimpulkan bahwa tindakan yang dilakukan pada kelas VIIIA untuk meningkatkan keaktifan dan hasil belajar PKn melalui model pembelajaran kooperatif Jigsaw berhasil karena indikator kinerja penelitian terpenuhi. Sebelum tindakan dengan menggunakan model pembelajaran kooperatif Jigsaw, keaktifan siswa kelas VIIIA sebesar 73.43 dalam katagori aktif dan pada akhir siklus III sebesar 79.10 dalam katagori sangat aktif, meningkat sebesar 5.67 (meningkat 8%). Sebelum dilakukan tindakan ketercapaian KKM pada kelas tersebut adalah 10%, setelah tindakan siklus I menjadi 54.33% (meningkat 43.33%), setelah tindakan siklus II menjadi 76.67% (meningkat 23.34% dari siklus I), dan setelah tindakan siklus III meningkat menjadi 93.33% (meningkat 16.66% dari siklus II).